PENERAPAN SPI–COSO ATAS PEMBERIAN KREDIT DANA BERGULIR KOTAKU - Dheo Rimbano (Jurnal Manajemen Kompeten, 2018)
“Kota Tanpa Kumuh” (KOTAKU) program is an advanced program of National Community Empowerment Program of Urban Mandiri that has accelerated program for handling urban slums and reducing poverty and so KOTAKU provides access to financial services for poor households by market – based micro loans with many activities which generate income that usually don’t have any access to other loan sources, to improve their economic conditions and activities those support economic growth and micro business , besides that teach them in managing loans and use it correctly.nevertheless, KOTAKU isn’t micro finance program, KOTAKU role only builds sustainable basic solutions for loan services and non – loan services at the “kelurahan” level. This research goal is to describe whether internal control system credit application applied to KOTAKU has been in accordance with the elements of internal control based on Committee Of Sponsoring Organizations (COSO). The method was used in this research is qualitative method, qualitative method is usually called as naturalistic research method because the research was conducted in the natural conditions, it’s also called as ethnography method, because in the beginning, this method is more widely used for research in cultural anthropology, it’s called as qualitative research because data have been collected and its analysis is more qualitative. The finding results is rolling loan lending system that is conducted by KOTAKU has completed internal controlling aspects based on COSO, except control activities components in the elements of separation of duties, namely lending isn’t separate from the loan inspection , and supervision component on the element of internal auditing that is internal which is not separate by LKM. And the recommendation can be given those are (1) giving and checking loans, and (2) internal auditing should be separated by LKM officer so that there is no collusion and irregulaties.